Perancangan Dan Implementasi Headlamp Pada Sepeda Motor Sebagai Pengatur Jarak Aman Pancaran Cahaya Dengan Menggunakan Sistem Led Matrix - Allif Maulana; Rizal Maulana; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Lighting on motor vehicles with light emission control systems is essential today. So made a headlamp system that is able to control the light emitted without the need for control of the user of the vehicle. Making this lamp system using a webcam camera is useful to read the condition of the road that will be skipped, then a microcomputer used to process the results of the condition of the road using the opencv library with the method of hough circle transform to detect other riders. From the results of the vehicle detection is used to condition a led light that has been arranged in parallel to regulate the light emission so that other riders do not glare when intercepting with the user system led matrix. From the test results obtained that the system is able to detect the vehicle by using the light beam as a reference other vehicles. Control of led matrix lamps can work with predetermined conditions. And the result of system validation explains that video input from webcam camera can be used to control the led matrix lamp with valid.